Synthesis and Characterization of CuO and NiO Nanoparticles Derived from Schiff Base Complexes - Bader, Ali Taleb; Al-qasii, Nada Ahmed Rasheed; Khaleel, Asmaa Mohammed Noori (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This study reports the synthesizes of such as copper oxide (CuO) and nickel oxide (NiO) nanoparticles (NPs) by thermal decompositions of Schiff base complexes and their physical characterization. A polydentate Schiff base ligand, (E)-2-(((2-chlorobenzyl)imino)methyl)phenol (CIMP), was synthesized by condensing 2-chlorobenzylamine and 2-hydroxybenzaldehyde. The ligand was identified by melting point, FT-IR, UV-Vis, and (1H and 13C NMR) spectroscopy. Cu(II) and Ni(II) complexes were prepared by reacting CIMP with the corresponding molar ratio in a 1:1 (metal: ligand). The complexes (Com1 and Com2) were characterized by melting point, FT-IR, and UV-Vis spectroscopy. The FT-IR spectra of the (Com1 and Com2) showed that the deprotonated CIMP ligand coordinated to the Ni(II) and Cu(II) metal ions through the azomethine nitrogen, aryl chloride, chlorine, and phenolic oxygen atoms. To determine the crystalline structure of the synthesized products, X-ray powder diffraction (XRD) and scanning electron microscopy (SEM) techniques were employed. The formation of copper oxide and nickel oxide as the new products was confirmed by XRD analysis. SEM imaging revealed the uniform and spherical morphology of the nanoparticles, which exhibited a remarkably narrow size distribution with an average diameter of 20 to 22 nm, highlighting their exceptional precision